Concentration and dynamics of two early fly embryo morphogens, Bicoid and Capicua, explored by FCS - Lili Zhang (My University, 2022)
Morphogens (often acting as transcription activators or repressors) govern pattern formation and cell differentiation during early embryogenesis. Abnormal distributions of morphogens can result in developmental defects or even death. Oftentimes, thresholds of concentrations of morphogens behave like an ON/OFF switch for the activation or repression of downstream genes. Accurate measurements of morphogen concentration and mobility in space and time can help tackle the puzzle of how exactly cascades of hundreds of morphogens coordinate their targets precisely and promptly amidst crowded and complicated cellular environments. The research question at the centre of my thesis is that of the concentration and dynamics of two morphogens with opposite functions in the early fly embryo. In the work presented in this thesis, we use Fluorescence Correlation Spectroscopy (FCS) and confocal imaging to achieve extremely low ($\sim$ nM) concentration measurements in live \textit{Drosophila} embryos expressing recombinant fluorescent morphogens, by carefully taking into account background noise and photobleaching effects. The dynamics of both Bicoid (Bcd) and Capicua (Cic), an activator and a repressor morphogens, were further studied using FCS, Fluorescence Recovery After Photobleaching (FRAP) and Monte Carlo simulation. We found that both types of morphogens are very mobile in nuclei, explaining how they are able to turn on or off gene expression in only a few minutes. However, these two morphogens with opposite functions have drastically different nucleo-cytoplasmic transport behaviours, where the activator can pass through the nuclear envelop (NE) relatively freely while the repressor is jailed inside nuclei during interphase. These findings can provide clues to distinguish between several hypothetical models (including the newly proposed hub hypothesis) trying to explain the mechanisms of target gene search and transcription regulation. In this thesis, a background introduction on transcription factors and morphogens is given in Chapter 1, with a focus on the two transcription factors (the activator Bicoid and the repressor Capicua) studied in this thesis. Next, experimental details such as fruit fly maintenance, and fluorescent techniques used to measure concentration and mobility are described in Chapter 2. From Chapter 3 to Chapter 5, three manuscripts from the thesis author, either published or in preparation for submission are presented in sequence. Chapter 3 introduces a new method to accurately measure protein concentration in the presence of noise and photobleahing in early \textit{Drosophila} embryos using FCS. Chapter 4 contains the results of concentration and mobility measurements for Cic which contribute to the finding that Cic acts like a fast brake in transcription repression. Chapter 5 compares the similarities and differences of the dynamics of Bcd and Cic through multiple lenses. Finally, a conclusion and future outlook are given in Chapter 6.
PhD Thesis
Keywords: Morphogen; Transcription factor; Concentration; Dynamics